The Effect of Tumor Characteristics and Location on the Extent of Lymph Node Metastases of Head and Neck Cutaneous Squamous Cell Carcinoma - van Leer, Bram; Leus, Alet J. G.; van Dijk, Boukje A. C.; van Kester, Marloes S.; Halmos, Gyorgy B.; Diercks, Gilles F.H.; van der Vegt, Bert; Vister, Jeroen; Rácz, Emoke; Plaat, Boudewijn E. C. (Frontiers in Oncology, 2022)
Background: The extent of the advised neck dissection for patients with metastasis of cutaneous squamous cell carcinoma of the head and neck (HNcSCC) is still subject to debate and no clear guidelines have been provided. To provide some guidelines this study aims to identify which tumor characteristics of HNcSCC can predict the pattern and extent of lymph node metastasis (LNM). Method: In this cohort study 80 patients who underwent a primary neck dissection for LNM of HNcSCC between 2003 and 2018 in the University Medical Center Groningen, the Netherlands, were included. Retrospective data was collected for primary tumor characteristics and LNM based on surgical and follow-up data. Influence of tumor characteristics on the extent of LNM was analyzed using non-parametric tests. Logistic regression analysis calculated odds ratios was used to identify a metastasis pattern based on the primary tumor location. Results: Only primary tumor location was associated with the pattern of LNM. HNcSCC of the ear metastasize to level II (OR = 2.6) and parotid gland (OR = 3.6), cutaneous lip carcinoma to ipsilateral and contralateral level I (OR = 5.3) and posterior scalp tumors to level II (OR = 5.6); level III (OR = 11.2), level IV (OR = 4.7) and the parotid gland (OR = 10.8). Ear canal tumors showed a low risk of LNM for all levels. The extend of LNM was not related to age or any tumor characteristics i.e. tumor diameter, infiltration depth, differentiation grade, perineural growth and vascular invasion. Conclusion: Primary tumor location determines the LNM pattern, whereas unfavorable tumor characteristics are not associated. Location guided limited neck dissection combined with parotidectomy will treat most patients adequately.